Effect of ellagitannin metabolites ellagic acid and urolithins A-D on the non-enzymatic glycation of human serum albumin and inhibiting mechanisms - Chunyan Peng; Wenna Zhou; Xing Xie; Feiyan Lu; Linju Xu; Qinghui Wen; Zongcai Tu; Lu Zhang (Food Science and Human Wellness)
Effect of ellagitannins gut microbiota metabolites ellagic acid (EA) and urolithin A-urolithin D (UroA-UroD) on human serum albumin (HSA) glycation were firstly evaluated in this research. The inhibition mechanisms were investigated by methylglyoxal (MGO) trapping and radical scavenging ability assays, docking studies and nano LC-orbitrap-MS/MS technology. Results indicated that the inhibition of urolithins on HSA glycation was highly positive correlated with the number of phenolic hydroxy groups. Addition of UroD and EA could effectively enhance the content of free amino group, suppress dicarbonyl compounds and advanced glycation end-products (AGEs) formation, alleviated tryptophan and protein oxidation, inhibited HSA amyloid-like aggregation. They could also trap MGO and scavenge 1,1-diphenyl-2-picrylhydrazyl free radical (DPPH·) and 2,2’-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid free radical (ABTS+·). Molecular docking indicated that EA and UroA-UroD interact with HSA mainly through hydrogen bound and hydrophobic interaction, among which 2 or 3 hydrogen bonds were formed. The number of glycation sites were reduced from 11 to 10, 10, 7, and 10, respectively, when 90 μmol/L of EA, UroA, UroC and UroD were added. However, weak inhibition was observed on UroA and UroB. These findings can provide scientific evidence for the application of ellagitannins-rich foods in alleviating diabetic complications.